Pore Formation Mechanism in Water Granulated Blast Furnace Slag - MON-NA, Izumi; OKAMOTO, Akira; NAGAO, Yoshikazu; TOKUMARU, Hideyuki; SUZUKI, Syohei; MYOZIN, Sei-ichi (Transactions of the Iron and Steel Institute of Japan, 1983)
The pore formation mechanism in water-granulated blast furnace slag and the effect of granulation conditions on the specific gravity of granulated slag are described. The gases released from molten-slag droplets into cooling water during slag granulation consist of H2 and N2 gases. The gases contained in the closed pores of granulated slag are mainly composed of H2 and N2 gases, the H2/N2 ratio being approximately 1.8. As the nitrogen content of molten slag increases, the amount of pores formed in granulated slag increases. This indicates that the dissolved nitrogen generates the H2 and N2 gases. It has been confirmed by an experiment using the heavy water as a tracer that cooling water can dissolve in molten-slag droplets in the extremely short time during solidification of the molten-slag droplets. From these results, the pore formation mechanism in granulated slag is presumed as follows. Cooling water dissolves in molten-slag droplets, reacts with nitrogen in the molten-slag droplets and evolves H2 and N2 gases by the reaction expressed by the following equation; 2N3-+3H2O=3H2+N2+3O2- Some of these gases are captured by the molten-slag droplets to form pores in granulated slag. This work has clarified the effect of granulating conditions (water quantity, water-jet velocity, water temperature and molten-slag temperature) on the specific gravity of granulated slag. The specific gravity increases as the water quantity and water jet velocity increase and the water temperature and molten-slag temperature decrease. These granulating conditions affect the time or temperature of the gas evolution reaction mentioned above.